2008
DOI: 10.1002/ird.426
|View full text |Cite
|
Sign up to set email alerts
|

A new method for creating maps of artificially drained areas in large river basins based on aerial photographs and geodata

Abstract: With regard to the creation of river basin plans and programmes of measures according to the EU Water Framework Directive, the importance of model-supported analyses of nutrient inputs into aquatic systems and the localization of source areas is increasing. Especially in lowland regions artificial drainage installations play a major role, but little information exists concerning their location within larger river basins. Therefore, artificially drained lands were identified by interpreting aerial photographs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Previous studies also identified uncertainties. Tetzlaff, Kuhr, and Wendland () noted the difficulty of acquiring aerial images at the right time associated with rainfall events and vegetation growth for a large area. Sugg's () GIS analysis based on soil drainage class and land cover in the Midwest United States overestimated total SD in Minnesota by 3,643 km 2 compared to the 1992 National Resource Inventory (NRI) including inflated estimates of SD for the RRB region.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also identified uncertainties. Tetzlaff, Kuhr, and Wendland () noted the difficulty of acquiring aerial images at the right time associated with rainfall events and vegetation growth for a large area. Sugg's () GIS analysis based on soil drainage class and land cover in the Midwest United States overestimated total SD in Minnesota by 3,643 km 2 compared to the 1992 National Resource Inventory (NRI) including inflated estimates of SD for the RRB region.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent information about tile drains is missing and only exists on the regional scale (Tetzlaff et al, 2009). At the national scale, however, there are no maps on tile drains.…”
Section: Discussion Of Model Uncertaintymentioning
confidence: 99%
“…www.nature.com/scientificdata www.nature.com/scientificdata/ Generally, the usefulness of scientific data mainly depends upon the level of accuracy and the quality of validation data. Most of the previous studies identified tile drained croplands at a smaller scale (field, catchment, or watershed scale) than the present study and employed GIS-based, remote-sensing-based or data-intensive methods like machine learning approaches 25,29,32 to achieve an overall accuracy of 79% to 86%. The availability and the spatial extent of validation data is the major constraint to these studies.…”
Section: Technical Validationmentioning
confidence: 97%